2014
DOI: 10.1016/j.najef.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of US financial and trade shocks to Asian economies: Implications for spillover of the 2007–2009 US financial crisis

Abstract: This paper describes an investigation of the transmission of US shocks to Asian economies with consideration of financial linkages and trade linkages. Using the sign restriction vector autoregression (VAR) approach during 2000-2012, our empirical results can be summarized as follows. First, both US financial and trade linkages exert a significant impact on production in Asian economies. Second, through both financial and trade linkages, US spillover shocks account for around 50% of the production fluctuation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 26 publications
(29 reference statements)
2
9
0
Order By: Relevance
“…One can also infer from such analysis which asset class/market is the most influential in transmitting volatilities to other domestic asset classes and to other markets in international investing (Liow, 2013). Moreover, the Asian financial crisis of 1997-1999 and the subprime mortgage/global financial crisis of [2007][2008][2009] indicated that volatility spillovers could be widespread across countries during turmoil periods (Yamamoto, 2014;Zhang, Li, & Yu, 2013). Finally, the inclusion of public real estate in this study reflects the increasing important role of this new "asset" class in domestic and international financial markets and reinforces the contribution of our work.…”
Section: Introductionsupporting
confidence: 74%
“…One can also infer from such analysis which asset class/market is the most influential in transmitting volatilities to other domestic asset classes and to other markets in international investing (Liow, 2013). Moreover, the Asian financial crisis of 1997-1999 and the subprime mortgage/global financial crisis of [2007][2008][2009] indicated that volatility spillovers could be widespread across countries during turmoil periods (Yamamoto, 2014;Zhang, Li, & Yu, 2013). Finally, the inclusion of public real estate in this study reflects the increasing important role of this new "asset" class in domestic and international financial markets and reinforces the contribution of our work.…”
Section: Introductionsupporting
confidence: 74%
“…Among the big and economically dominant states, CA and New York receive shocks from only three states. Studies show that big and economically powerful entities, given their dominant nature, are more immune to shock spillovers than their smaller counterparts (Yamamoto, 2014; Sugimoto et al , 2014). Our findings also show that California, which is one of the largest economies in the world, is immune from the fourth level value shock (crisis) except Texas, also another large state in the US.…”
Section: Empirical Results – Financial Contagion Risk Analysismentioning
confidence: 99%
“…Chen et al (2014) study the stock market integration between frontier and leading markets during the periods of pre-and post-global financial crisis. Črnigoj and Verbič (2014), Teixeira et al (2014), Yamamoto (2014) and Wan and Jin (2014) …”
Section: Monetary Policy Announcementsmentioning
confidence: 99%